Low-impact scenarios may account for two-thirds of blunt traumatic aortic rupture. Issue 5 (4th May 2010) - Sastry, P; Field, M; Cuerden, R; Richens, D
Abstract : Background: Traditionally, blunt traumatic aortic rupture (BTAR) is thought to be a high-velocity injury. It was hypothesised that BTAR has a higher than suspected incidence in low-speed accidents, with unique kinematic and demographic risk factors. Methods: Using the UK Cooperative Crash Injury Study (CCIS) framework, impact profiling was undertaken for accidents involving BTAR. Equivalence Test Speed (ETS) was the parameter used to compare crash severity within comparable impact configurations, as it is a surrogate marker reflecting the net impact forces acting on the vehicle. ETS=40 mph (the threshold used for safety testing within the EURONCAP scheme) was used to delineate low-impact blunt traumatic aortic rupture (LIBTAR) cases, which were subsequently analysed for aetiological risk factors. Results: 119 fully analysed cases of aortic injury were identified from a total of 16 444 cases reported to the UK CCIS between 1998 and 2007. 79 cases (66.4%) qualified as LIBTAR. Risk factors for LIBTAR were age >60 (p<0.0001), lateral impact direction (OR 2.041, RR 1.99, p=0.003), and struck side seat position (OR 1.934, RR 1.885 p=0.101). Low-impact crash scenarios were found to represent more than 95% of UK road traffic accidents. Conclusion: Low-impact collisions account for two thirds of fatal aortic injuries. Age >60, lateral impacts and struck side seat position are predictive of LIBTAR. Low-impact cases were associated with minor (potentially subclinical) intimomedial injuries. Therefore, it is recommended that a higher index of suspicion of aortic injury is used in low-impact scenarios in the risk groups identified.